Queen Shima as Nusantara feminist pioneer: Feminist literary study on the novels Putri Kalingga and Avatar Keadilan - Wiyatmi, Wiyatmi; Sudiati, Sudiati; Artanti, Yeni (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2024)
Up to the present time, the public is more familiar with the figures of Kartini, Dewi Sartika, and Cut Nyak Dien as icons of Indonesian women emancipation fighters. In reality, for hundreds of years before Kartini was born, in the 7th century, the Kingdom of Kalingga has been led by a woman, Queen Shima. Not much of the historical data has recorded her name and roles. In the midst of this condition, there were published two novels which enumerate the way of life of Queen Shima, entitled Putri Kalingga (Wibidharma, 2022) and Avatar Keadilan: Pesona Kebajikan Maharatu Shima dari Negeri Kalingga (Nararosa, 2010). The present study is aimed at understanding the existence of Queen Shima as a pioneer of Nusantara feminism by using the perspectives of feminist literary approach. The study was qualitative feminist research. The data sources of the study were the two novels Putri Kalingga and Avatar Keadilan: Pesona Kebajikan Maharatu Shima dari Negeri Kalingga. Data were the narratives that tell about the characteristics and way of life of Queen Shima as King of Kalingga Kingdom which contain information about her position and roles in Nusantara women history. Findings of the study show that Queen Shima, whose life story is told in the two novels Putri Kalingga and Avatar Keadilan is not only a fictitious character, but also a historical figure from the 7th century, who is hauled up as King of Kalingga Kingdom not because of inheriting the crown from her parents, but because of the intelligence, wisdom, and leardership capacities she has. In the perspectives of feminist literary criticism, Queen Shima represents Nusantara feminisim that has been practiced in the era of the Kalingga kingdom.